Grounds for Restricting the Free Movement of Workers – Recognition of Previous Professional Experience and Loyalty to the Employer - Vinzenz, Verena (Maastricht 30: A Central European Perspective, 2025)
This article analyzes and critiques two European Court of Justice (ECJ) judgments concerning the freedom of movement for workers and the justifications for restrictions on this right. The Krah judgment is critically examined for its combination of two distinct provisions to constitute a restriction, while the reasoning in the Land Niedersachsen case, involving a single provision under a Collective Agreement,is supported. The article further explores the ECJ’s evolving approach to company loyalty as a justification, noting a significant development in the Land Niedersachsen judgment. The Court’s decision to consider functionally independent units within a single employer context as invalidating company loyalty justification represents a progression from the SALK ruling. Lastly, the article assesses the ECJ’s treatment of recognizing previous professional experience, particularly in the Krah ruling, where limited recognition was deemed unjustifiable due to the continual accumulation of expertise by academic staff. The case of Land Niedersachsen introduces a nuanced perspective, emphasizing the inconsistency in the employer’s recognition of equivalent experience. Together, these cases provide a deeper understanding of the permissible boundaries of justifications in EU law.Keywords: Freedom of Movement of Workers, Art 45 TFEU, Restriction, Justification, Company Loyalty, Professional Experience